Association of Inpatient Initiation of Sacubitril/Valsartan With Short and Intermediate-Term Readmissions in Patients Hospitalized for Heart Failure: A Retrospective Cohort Study - Waqas, Shamaiza; Raymond, Catherine; Arshad, Khurram; Gunaseelan, Luxhman; Opaleye, Taiwo; Klein, Jacob; Malik, Dua; Collins-Hamel, Benjamin (Cardiology and Cardiovascular Medicine, 2026)
Background: Sacubitril/valsartan improves outcomes in heart failure with reduced ejection fraction (HFrEF), but real-world data on its effect on hospital readmissions after inpatient initiation are limited. Methods: We conducted a retrospective cohort study of adults hospitalized with HFrEF across multiple Southeast Michigan hospitals between October 2017 and October 2024. Patients initiated on sacubitril/ valsartan during hospitalization and discharged on therapy were compared with contemporaneous controls not treated with sacubitril/valsartan. Readmissions at 30, 60, and 90 days were assessed. Results: A total of 164 patients initiated on sacubitril/valsartan and 16 control patients were included. Baseline ejection fraction distribution was similar between groups. Readmission rates in the sacubitril/valsartan group were 18.9% at 30 days, 15.8% at 60 days, and 12.7% at 90 days. Compared with controls, sacubitril/valsartan initiation was associated with a significantly lower 60-day readmission rate (p = 0.04), while differences at 30 and 90 days were not statistically significant. Conclusion: Inpatient initiation of sacubitril/valsartan was associated with reduced 60-day readmissions in patients hospitalized with HFrEF, with no significant effect at 30 or 90 days. These findings suggest a potential intermediate-term benefit and support early initiation during hospitalization, although confirmation in larger prospective cohorts is needed